Biosynthesis and Anti-inflammatory Activity of Zinc Oxide Nanoparticles Using Leaf Extract of Senecio chrysanthemoides. (11th April 2023) - Zahoor, Sana; Sheraz, Sadia; Shams, Dilawar Farhan; Rehman, Gauhar; Nayab, Saira; Shah, Muhammad Ishaq Ali; Ateeq, Muhammad; Shah, Said Karim; Ahmad, Tanveer; Shams, Sulaiman; Khan, Waliullah
Abstract : Nanotechnology has recently appeared as an important study subject in modern material sciences. Greener synthesis of nanoparticles has gained the attention of many scientists because of its integral characteristics such as effectiveness, eco-friendly, and low cost. In the present study by following the green synthesis approach, zinc oxide nanoparticles (ZnO NPs) were formed for the very first time by using Senecio chrysanthemoides leaf extract as a reducing agent. The UV-Vis spectrophotometer was used to study the synthesized ZnO NPs, and the specific peak was found to be at 349 nm. The characteristic Fourier transform infrared (FTIR) peak was found to be at 449 cm -1 which displays the peak of ZnO molecules. The surface morphology of the ZnO NPs was determined via scanning electron microscopy (SEM). The energy-dispersive X-ray spectroscopy (EDX) study showed that the synthesized ZnO NPs are present at the weight percentage of 66.38%. The X-ray diffraction (XRD) spectrum confirmed the hexagonal phase wurtzite structure, with the average particle size of 31 nm, and demonstrated the crystalline structure of ZnO NPs. Additionally, to all these experiments, we compared the anti-inflammatory properties of biogenic ZnO NPs to a standard drug. Biosynthesized ZnO NPs have revealed an effective anti-inflammatory activity at a higher concentration (100 mL -1 ) and showed 73% inhibition in comparison with diclofenac sodium drug. Zinc oxide was shown to be compatible with diclofenac sodium, according to the results. The ZnO NPs produced using the greener synthesis process have the potential to be used in a broad range of fields and also used as a good anti-inflammatory agent.